2022
DOI: 10.6065/apem.2142112.056
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25-hydroxyvitamin D level is associated with obesity and atherogenesis in adolescent boys

Abstract: Low serum 25-hydroxyvitamin D levels are associated with obesity and atherogenesis in adolescent boysRunning title: Low serum 25(OH)D and obesity and atherogenic risk in adolescents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A population-based study conducted in Norway showed an inverse relationship between low serum 25(OH)D levels and increased BMI [90]. In various other studies, increased body fat and higher BMI are shown to be highly related to 25(OH)D levels [91][92][93][94]. Various meta-analyses have shown an inverse relationship between body weight and vitamin D levels; however, this relationship remains largely confusing due to confounding studies warranting more in-depth research studies to definitively prove the association [91].…”
Section: Other Micronutrientsmentioning
confidence: 96%
See 2 more Smart Citations
“…A population-based study conducted in Norway showed an inverse relationship between low serum 25(OH)D levels and increased BMI [90]. In various other studies, increased body fat and higher BMI are shown to be highly related to 25(OH)D levels [91][92][93][94]. Various meta-analyses have shown an inverse relationship between body weight and vitamin D levels; however, this relationship remains largely confusing due to confounding studies warranting more in-depth research studies to definitively prove the association [91].…”
Section: Other Micronutrientsmentioning
confidence: 96%
“…Various meta-analyses have shown an inverse relationship between body weight and vitamin D levels; however, this relationship remains largely confusing due to confounding studies warranting more in-depth research studies to definitively prove the association [ 91 ]. Most studies show that supplementation with vitamin D does not have an effect on body weight or BMI but does affect body fat distribution [ 92 , 93 ]. In a study on Japanese adolescents, it was shown that low serum vitamin D levels are associated with obesity and atherogenesis in adolescent boys only and not adolescent girls; hence future studies are warranted to establish a concrete relationship [ 92 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D deficiency in childhood and adolescence has been associated with multiple sclerosis (MS) and prediabetes, which are also linked to obesity [ 9 , 29 ]. Adolescent boys with low serum 25-hydroxyvitamin D levels were more likely to be obese and have an increased risk of atherogenic events [ 64 ]. The mechanisms underlying low levels of vitamin D are unclear.…”
Section: Skeletal Comorbiditiesmentioning
confidence: 99%
“…The results of this study provide evidence that low serum 25(OH)D 3 levels are positively associated with the risk of obesity and atherogenesis in Japanese adolescent boys, but not in girls [ 11 ]. This sex difference was presumed to be related to body composition, sun exposure, puberty.…”
mentioning
confidence: 99%